Influence of the nano-WC content and Sintering Temperature on the Phase Composition of Hard Alloys in the System TiC–WC–VC–NiCr - Pukas, S.; Zinko, L.; German, N.; Gladyshevskii, R.; Koval, I. V.; Bodrova, L.; Kramar, H.; Marynenko, S. (Physics and Chemistry of Solid State, 2020)
The effect of the WC content and the sintering temperature, as the main technological factor, on the phase composition of TiC–xWC–5VC–18NiCr alloys was investigated by X-ray phase analysis. It was established that the main phases in the investigated alloys were the NaCl-type quaternary (Ti,V,W)C phase and a solid solution of Cr in Ni. Depending on the size of the WC particles used for the preparation, the metal binder could be described by the formula Ni0.75Cr0.25 (for nano WC) or Ni0.5Cr0.5 (for fine-sized WC). In alloys prepared with fine-sized WC, elementary Cr and traces of the Cr3C2 and Cr23C6 were also found. With increasing content of nano-sized WC and sintering temperature the solubility of W in (Ti,V)C increased. No W2C phase was detected under the conditions of the investigation.